The behaviour of Bewick’s Swans at the Welney Wildfowl Refuge, Norfolk, and on the surrounding fens: a comparison - Scott, D K (Wildfowl, 1980)
This paper describes the general behaviour of Bewick’s Swans Cygnus columbianus bewickii at the Welney Wildfowl Refuge, on the Ouse Washes, Norfolk, and compares this with the behaviour of the swans on surrounding fenland. On the fens, the swans were at lower densities and interacted aggressively less often during feeding than in front of the observatory, although, on the fens, they spent more time feeding throughout the day. In addition, fen flocks contained more cygnets than those in front of the observatory. This was because pairs spent more time on the fens in years when they had cygnets than when they did not. However, there were few differences in other aspects of social behaviour, and no evidence of differential mortality or breeding success between swans spending much time on the refuge and those spending little time there.